Answer:
Simplifying
2(4z + -3 + -21) = 166 + -46
Reorder the terms:
2(-3 + -21 + 4z) = 166 + -46
Combine like terms: -3 + -21 = -24
2(-24 + 4z) = 166 + -46
(-24 * 2 + 4z * 2) = 166 + -46
(-48 + 8z) = 166 + -46
Combine like terms: 166 + -46 = 120
-48 + 8z = 120
Solving
-48 + 8z = 120
Solving for variable 'z'.
Move all terms containing z to the left, all other terms to the right.
Add '48' to each side of the equation.
-48 + 48 + 8z = 120 + 48
Combine like terms: -48 + 48 = 0
0 + 8z = 120 + 48
8z = 120 + 48
Combine like terms: 120 + 48 = 168
8z = 168
Divide each side by '8'.
z = 21
Simplifying
z = 21